2016
DOI: 10.1002/ajh.24578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing for JAK2, MPL, and CALR in myeloproliferative neoplasms

Abstract: Polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are myeloproliferative neoplasms characterized by recurrent somatic mutations in JAK2, CALR, and MPL. This short review addresses (1) the spectrum of mutations seen in PV, ET, and PMF, (2) the emerging genotype-phenotype correlations, (3) the current role of molecular testing in disease classification and management, and (4) several important considerations for selecting an appropriate molecular test. In our view, sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Mutations are now formally integrated into the WHO diagnostic criteria for PMF and other MPN . In this regard, a diagnosis of PV often requires demonstration of an associated JAK2 mutation and diagnosis of ET and PMF is strongly supported by the presence of JAK2 , CALR or MPL mutations; however, these mutations are not disease‐specific and their presence is not essential for an otherwise morphology‐based diagnosis . Genetic markers in PMF have also proven to be the primary determinants of survival and are now part of formal prognostic systems, such as MIPSS70+ version 2.0 and GIPSS; in this regard, ASXL1 and SRSF2 mutations and unfavorable karyotype have consistently been associated with inferior survival.…”
Section: Closing Commentsmentioning
confidence: 99%
“…Mutations are now formally integrated into the WHO diagnostic criteria for PMF and other MPN . In this regard, a diagnosis of PV often requires demonstration of an associated JAK2 mutation and diagnosis of ET and PMF is strongly supported by the presence of JAK2 , CALR or MPL mutations; however, these mutations are not disease‐specific and their presence is not essential for an otherwise morphology‐based diagnosis . Genetic markers in PMF have also proven to be the primary determinants of survival and are now part of formal prognostic systems, such as MIPSS70+ version 2.0 and GIPSS; in this regard, ASXL1 and SRSF2 mutations and unfavorable karyotype have consistently been associated with inferior survival.…”
Section: Closing Commentsmentioning
confidence: 99%
“…Besides JAK2V617F mutation, recent studies showed that somatic mutation at exon 9 of CALR accounts of 50~80% JAK2V617F-negative ET and MF patients. [5][6][7][8][9] It has diagnostic importance and also contributes to the clinical characteristics of ET patients; therefore, it is crucial to identify the mutations. [10][11][12][13][14][15] Although most of the mutations correspond to a 52 bp deletion (type 1) or a 5 bp insertion (type 2), there were more than 50 other mutations found.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14] Standard procedures were followed for driver mutation screening. 15 April 2018 and data collected via medical records or in certain cases, by directly contacting patients or their physicians. Risk-stratification was performed using the three-tiered prognostic model international prognostic score for ET (IPSET).…”
Section: Methodsmentioning
confidence: 99%